Study of inter pedicular distance of lumbar spinal canal in perspective of lumbar canal stenosis using plain antero-posterior radiographs in western population of Rajasthan, India - Bhaumik, Meghna; Bhaumik, Uday (International Journal of Research in Medical Sciences, 2019)
Background: Various causes have been attributed to low backache, but lumbar canal stenosis is turned out to be a major causative factor. It has been suggested that reduced IPD is one among the major cause of narrowing of the spinal canal. The objective of this study was to evaluate the inter pedicular distances in lumbar vertebral column in both sexes of western Rajasthan, India. Methods: The present descriptive type study was conducted in Department of Anatomy and Neurosurgery Sawai Man Singh Medical College, Jaipur, Rajasthan, India. Antero-posterior plain radiographs of lumbar spine in 1000 subjects aged between 20 to 60 years and those who were born and brought up in Rajasthan state were used for the study. All measurements were made by using electronic digital Vernier caliper. Student t-test was used for analysis. Results: Mean transverse diameter of lumbar vertebral canal (I.P.D) is minimum at L1 vertebra in both sexes. The maximum values of I.P.D were recorded for vertebra L5 for both sexes. Conclusions: The values of IPD are higher in male population in comparison to female counterparts.